2018
DOI: 10.1111/aji.13021
|View full text |Cite
|
Sign up to set email alerts
|

Tokishakuyakusan, a traditional Japanese medicine (Kampo) mitigates iNKT cell‐mediated pregnancy loss in mice

Abstract: The findings in this study suggest that the inhibitory effects of TSS on pregnancy loss may involve immune modulation of iNKT cells during early pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Some researchers have demonstrated the ameliorative effects of TS on preeclampsia, fetal growth restriction, and recurrent pregnancy loss [29,30]. It has been reported that TS regulates the immunity of invariant natural killer T cells during early pregnancy (in mice), and thus reduces the rate of pregnancy loss [31]. The antihypertensive effects of TS have also been reported [29].…”
Section: Plos Onementioning
confidence: 99%
“…Some researchers have demonstrated the ameliorative effects of TS on preeclampsia, fetal growth restriction, and recurrent pregnancy loss [29,30]. It has been reported that TS regulates the immunity of invariant natural killer T cells during early pregnancy (in mice), and thus reduces the rate of pregnancy loss [31]. The antihypertensive effects of TS have also been reported [29].…”
Section: Plos Onementioning
confidence: 99%
“…[5][6][7] Currently, the mechanisms of TSS have been reported to involve immunological effects on murine endometriosis and pregnancy loss model. 8,9 These reports promisingly suggest that TSS may potentially contribute to management of endometriosis symptoms.…”
Section: Introductionmentioning
confidence: 95%
“…These results indicate the activated innate immune cells DCs and iNKT cells directly lead to miscarriage without microbial-associated inflammation. Interestingly, miscarriage and preterm birth induced by a-GalCer were ameliorated by treatment with rosiglitazone [58] and Tokishakuyakusan, a traditional Japanese medicine [109]. Innate immune cells, DCs, and iNKT cells are therefore associated with not only preterm both but also miscarriage in the absence of infection.…”
Section: Miscarriage and Infertilitymentioning
confidence: 99%